Natural Products for Neurodegeneration: Regulating Neurotrophic Signals. (22nd June 2021) - Uddin, Md Sahab; Mamun, Abdullah Al; Rahman, Md Motiar; Jeandet, Philippe; Alexiou, Athanasios; Behl, Tapan; Sarwar, Md Shahid; Sobarzo-Sánchez, Eduardo; Ashraf, Ghulam Md; Sayed, Amany A.; Albadrani, Ghadeer M.; Peluso, Ilaria; et al.
Abstract : Neurodegenerative disorders (NDs) are heterogeneous groups of ailments typically characterized by progressive damage of the nervous system. Several drugs are used to treat NDs but they have only symptomatic benefits with various side effects. Numerous researches have been performed to prove the advantages of phytochemicals for the treatment of NDs. Furthermore, phytochemicals such as polyphenols might play a pivotal role in rescue from neurodegeneration due to their various effects as anti-inflammatory, antioxidative, and antiamyloidogenic agents by controlling apoptotic factors, neurotrophic factors (NTFs), free radical scavenging system, and mitochondrial stress. On the other hand, neurotrophins (NTs) including nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF), NT4/5, and NT3 might have a crucial neuroprotective role, and their diminution triggers the development of the NDs. Polyphenols can interfere directly with intracellular signaling molecules to alter brain activity. Several natural products also improve the biosynthesis of endogenous genes encoding antiapoptotic Bcl-2 as well as NTFs such as glial cell and brain-derived NTFs. Various epidemiological studies have demonstrated that the initiation of these genes could play an essential role in the neuroprotective function of dietary compounds. Hence, targeting NTs might represent a promising approach for the management of NDs. In this review, we focus on the natural product-mediated neurotrophic signal-modulating cascades, which are involved in the neuroprotective effects.